Sales Marketing Strategy at Outlet Kopi 48 Buah Batu Using Business Model Canvas - Sulistiawan Satria; Keni Kaniawati (Jurnal Ilmu Manajemen Profitability, 2024)
This research aims to analyze the Marketing Strategy in Increasing Sales at Coffee 48 Buah Batu Outlet using the BMC strategy. The research type is qualitative descriptive, using secondary data from questionnaires with 20 respondents. The data analysis technique used is SWOT analysis. The results of the research indicate that the implementation of the BMC-based marketing strategy at Coffee 48 Buah Batu Outlet has been successful in helping the outlet compete with its competitors in the coffee industry and create a competitive advantage. Positive consumer responses to product innovations, the use of social media, collaborations with local producers, and fast and convenient service have provided strong support for the success of this strategy. Additionally, the results of the SWOT analysis show that an in-depth understanding of customers, the utilization of technology, product and service differentiation, and smart collaborations are the key strengths that have been able to cover and address weaknesses and threats faced by the outlet. Thus, the BMC-based marketing strategy has helped Coffee 48 Buah Batu Outlet achieve a competitive advantage and become a relevant and successful player in the busy coffee industry.